Krievu pareizticīgā baznīca un normatīvā vara Krievijas Federācijas ārpolitikā - Kudors, Andis (Latvijas Universitāte, 2011)
Maģistra darbs „Krievu pareizticīgā baznīca un normatīvā vara Krievijas Federācijas ārpolitikā” ir veltīts Krievijas normatīvās ārpolitikas izpētei. Darba ietvaros tiek pētīta Krievu pareizticīgās baznīcas (KPB) darbība starptautiskajā arēnā, kur tā piedāvā koriģēt patreizējo starptautisko attiecību normatīvo bāzi, balstoties uz „civlizāciju dialoga” idejām. „Civilizāciju dialoga” institucionalizēšana starptautiskajās attiecībās, nozīmētu atteikšanos no noteiktu cilvēktiesību un citu vispāratzītu starptautisko juridisko normu un principu universāluma. Tas, savukārt, mazinātu Rietumu normatīvo aktieru spēju īstenot normatīvo varu starptautiskajā arēnā. Dotā darba mērķis ir izpētīt, kā Krievu pareizticīgās baznīcas iesaiste valsts ārpolitkā ietekmē Krievijas normatīvās ārpolitikas īstenošanas praksi. Darbā ir paredzēts rast atbildi uz sekojošo izpētes jautājumu: vai Krievu pareizticīgās baznīcas, normatīvā aktiera, iesaiste ārpolitikā veicina Krievijas normatīvo mērķu sasniegšanu starptautiskajā arēnā? Tiek izvirzītas divas hipotēzes: 1) Krievu pareizticīgās baznīcas, kā normatīva aktiera, iesaiste valsts ārpolitikā vairo Krievijas ārpolitikas leģitimitāti un līdz ar to veicina tās normatīvo mērķu sasniegšanu; 2) pareizticības vērtību, kā normatīvās varas avotu, izmantošana ārpolitikā veicina Krievijas normatīvās ārpolitikas mērķu sasniegšanu. Darba teorētiskajā daļā tiek skatīti gan J.Mannersa, gan N.Toči un citu normatīvās varas teorētiķu darbi. Tāpat tiek analizēti arī „civilizāciju dialoga” konceptualizācijas mēģinājumi. Empīriskajā sadaļā tiek nedaudz apskatīta Krievijas normatīvā ārpolitika arī plašākā - Krievijas un Rietumu aktoru attiecību kontekstā, tomēr galvenā uzmanība tiek pievērsta tieši tām Krievijas normatīvās ārpolitikas aktivitātēm, kurās ir iesaistīta Krievu pareizticīgā baznīca. Kā gadījuma izpēte tiek analizētas KPB iniciatīvas ANO. Pētījumā tiek secināts, ka KPB iesaiste Krievijas ārpolitikā dod iespēju vairot Krievijas rīcības leģitmitāti un sasniegt normatīvās ārpolitikas mēķus, t.sk. diskusijas par „tradicionālajām vērtībām” aktualizēšanu un „civilizāciju dialoga” zināmu institucionalizēšanu. Ņemot vērā pētījuma rezultātus, tiek secināts, ka abas pētījuma sākumā izvirzītās hipotēzes tiek apstiprinātas. Atslēgvārdi: normatīvā vara, civilizāciju dialogs, tradicionālās vērtības, Krievu pareizticīgā baznīca.

SUMMARY The Master’s thesis The Russian Orthodox Church and Normative Power in Russian Foreign Policy is dedicated to the research of the Russian normative foreign policy. The operation of Russian Orthodox Church (ROC) in the international arena is studied, where it offers to adjust the current normative framework for international relations based on ideas of ‘dialogue of civilizations'. While the ‘dialogue of civilizations’ is not directly related to the theory of normative power, its’ institutionalization in international relations would mean the abandonment of universality of certain human rights and other commonly recognized international legal norms. This, in return, would reduce the capacity of Western normative actors to implement normative power in the international arena. So far, normative power has been mostly studied as the phenomenon of the European Union's foreign policy. However, in recent years more and more this approach is used by studying China, United States, Russia and other countries. The aim of this study is to examine how Russian Orthodox Church involvement in the State's foreign policy affects implementation of Russia's normative foreign policy. The paper is intended to answer the following research question: Does involvement of the Russian Orthodox Church, a normative actor, contributes to the achievement of Russian foreign policy normative objectives in the international arena? There are two hypotheses: 1) Russian Orthodox Church, as a normative actor, enhances the legitimacy of Russia's foreign policy by involvement in State's foreign policy and thus contributes to the achievement of its’ normative objectives; 2) the usage of values of Orthodoxy, as the source of normative power, in the foreign policy contributes to the achievement of normative objectives of Russian foreign policy. Thus, the theoretical part of this paper address Ian Manners and Nathaly Tocci and works of other normative power theorists. Attempts of conceptualization of the ‘dialogue of civilizations’ are also analyzed. The empirical section covers Russia's normative foreign policy also a little bit more generally – in the view of the relationship between Russia and Western actors, yet focusing on the Russian normative foreign policy activities which involves Russian Orthodox Church. Similarly, the analysis of existing and eventual sources of Russian normative power focus on the orthodox values and related aspects of Russian identity. Empirical part of the study shows that the ROC activities meet the aspects of normative power theory. It had enabled the reach of normative objectives. Among them are debates on the partnership of civilizations and the importance of traditional values, adoption of the resolution in the UN Human Rights Council and establishment of the high level group in the UN. However, there are problems with reality and image of Russia as an Orthodox country proclamed by the ROC. In view of this and the results of the study, it is concluded that both hypothesis raised in the beginning of the study are confirmed. However, it is clear that religious values are not fully perceived as basis for changes of fundamental freedoms and human rights norms. Consequently, Russia's potential for substantial impact on the current views on democracy, rule of law and human rights in the European Union, Council of Europe, OSCE and UN should be critically evaluated. Keywords: normative power, dialogue of civilizatons, Russian foreign policy, The Russian Orhodox Church, traditional values
The Russian Orthodox Church and Normative Power in Russian Foreign Policy
Keywords: Politikas zinātne (politoloģija)